ANALISIS PERTUMBUHAN DAN FINANSIAL TANAMAN SUNGKAI (Peronema canescens) DI KAPUAS, KALIMANTAN TENGAH : Wahyudi - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2016)
ABSTRACT Forestry concession conduct the plantation project at the logged over areas using TPTI silvicultural system. The aim of this research was to analyze the growth and financial value of sungkai (Peronema canescens) that be planted at the logged over areas of PT Gunung Meranti at the Kapuas, Central Kalimantan Province, using TPTI silvicultural system. The research analyzed of 100 samples of sungkai and it analysed of its growth until 13 years old and estimate of financial value until 40 years old at the future with loan interest assumption 19,5% and 16%, expense increase 10%, price decrease 10% and the form factor 0,6. The living percentage of sungkai at the 13 years old namely 89,7%. Mean Annual Increment (MAI) namely 11,90 m3/ha/year, and the best financial cycle for the worker of wood company class namely 13 to 25 years. Keywords: Analyze, financial, growth, Peronema canescens